Evaluation of the small particle adhesion force on low temperature surface in high vacuum using atomic force microscopy. (1st August 2022) - Miwa, Takafumi; Hashizume, Tomihiro
Abstract : The adhesion force of small particles on a substrate surface depends on various parameters, including the surface roughness, temperature, and surrounding environment. In this study, atomic force microscopy was used to investigate the surface temperature dependence of the adhesion force of small silica particles on relatively smooth and rough Al substrates at temperatures below room temperature in high vacuum. The adhesion force did not depend on the temperature of the rough substrate. On the smooth substrate with a temperature decrease from 298 K, the adhesion force increased and was the largest at 273 K. Moreover, the adhesion force decreased from 273 to 213 K and remained almost constant below 213 K. The change in adhesion force was explained in terms of the surface diffusion of water molecules that formed capillaries. Its activation barrier was deduced to be 96 meV in the range of 273–213 K.